Peran Employability dalam Hubungan Job Insecurity dan Kepuasan Kerja - Mahaputra, Byarbreda; Riantoputra, Corina D. S.; Respati, Adi (Makara Human Behavior Studies in Asia, 2013)
Job insecurity is often thought to cause lower job satisfaction. However, research shows that the relationship between these two variables is more complicated than previously assumed. Previous studies fail to provide conclusive results, which indicate that the relationships between job insecurity and job satisfaction may be moderated by other variables. Two variables that can explainthis relationship are employability, defined as employees’ perception of their abilities to find a new job, and work status differences (i.e., permanent and contract employees). Therefore, this study hypothesizes that employability will moderate the relationship between job insecurity and job satisfaction for, both, permanent and contract employees. Adapting scales from previous research, this study conducted a cross-sectional survey of 172 employees, comprised of permanent and contract employees, of a logistic services company in Indonesia. Results reveal that employability moderates the relationship between job insecurity and job satisfaction among permanent but not contract employees. This paper also discusses the implication of these results for the advancement of organizational behavior theory, especially for understanding the impact of job insecurity on job satisfaction.